Finding Limits Algebraically

There are several ways to evaluate a limit:

  1. Using a table
  2. Based on a graph
  3. Using algebra to simplify

We've seen how to do the first two, and in this section, we'll see how we can use algebra to evaluate a limit without needing to build a table or draw a graph (which can be difficult for complicated functions).

Limit Laws

First, let's take a look at some rules that we can use to break limits down into simpler problems. It turns out, though, that we won't need to use these for long, because we'll quickly spot a shortcut. Since we won't actually use these limit laws to solve problems, for the most part, they are mostly included here just to show the foundation; they underlie the work we'll do later, but we won't need to show them after a quick example or two.

Two Basic Limits

Constant function: limxck=k\ans{\displaystyle\lim_{x \to c} k = k}

Identity function: limxcx=c\ans{\displaystyle\lim_{x \to c} x = c}

These two are pretty straightforward if you look at a graph: the constant function f(x)=kf(x) = k is simply a horizontal line, so no matter what values you plug in or approach, it always returns kk. Similarly, the identity function f(x)=xf(x) = x returns whatever input you give it, so as you plug in values closer and closer to cc, you receive back the same values, making the limit just equal to cc.

Limit Laws

Suppose that limxcf(x)=L\displaystyle\lim_{x \to c} f(x) = L and limxcg(x)=M\displaystyle\lim_{x \to c} g(x) = M. We can combine these in the following ways:

  1. Adding (or subtracting) two limits

limxc[f(x)+g(x)]=L+M\lim_{x \to c} \big[f(x) + g(x)\big] = L + M

  1. Multiplying by a constant

limxc[kf(x)]=kL\lim_{x \to c} \big[kf(x)\big] = kL

  1. Multiplying / dividing two limits

limxc[f(x)g(x)]=LM\lim_{x \to c} \big[f(x) \cdot g(x)\big] = L \cdot M

limxc[f(x)g(x)]=LM, as long as M = 0\lim_{x \to c} \left[\dfrac{f(x)}{g(x)}\right] = \dfrac{L}{M} \textrm{, as long as } M \ \cancel=\ 0

Let's see how we can apply these to evaluate limits. Basically, we can use these laws to break complicated expressions down into one of the two basic forms, then apply those definitions over and over.

Limit Laws

Use the limit laws to evaluate limx52x23x+4\displaystyle\lim_{x \to 5} 2x^2-3x+4.

Solution

Using the limit laws, start breaking this function down by splitting apart multiplication, addition, and subtraction: limx52x23x+4=limx52x2limx53x+limx54=2limx5x23limx5x+limx54=2(limx5x)(limx5x)3limx5x+limx54=2(5)(5)3(5)+(4)=39\begin{aligned} \lim_{x \to 5} 2x^2-3x+4 &= \lim_{x \to 5} 2x^2 - \lim_{x \to 5} 3x + \lim_{x \to 5} 4\ &= 2\lim_{x \to 5} x^2 - 3\lim_{x \to 5} x + \lim_{x \to 5} 4\ &= 2\left(\lim_{x \to 5} x\right)\left(\lim_{x \to 5} x\right) - 3\lim_{x \to 5} x + \lim_{x \to 5} 4\ &= 2(5)(5) - 3(5) + (4)\ &= \ans{39} \end{aligned}

You may notice something interesting about that last line before the answer, especially if you compare it to the original problem. Before we explore that fully, though, try another one like it.

  1. Use the limit laws to evaluate limx2x3+2x2153x\displaystyle\lim_{x \to -2} \dfrac{x^3 + 2x^2 - 1}{5-3x}

  2. limx2x3+2x2153x=limx2x3+2x21limx253x=(limx2x)(limx2x)(limx2x)+2(limx2x)(limx2x)limx21limx253limx2x=(2)(2)(2)+2(2)(2)153(2)=111\begin{aligned} \lim_{x \to -2} \dfrac{x^3+2x^2-1}{5-3x} &= \dfrac{\displaystyle\lim_{x \to -2} x^3+2x^2-1}{\displaystyle\lim_{x \to -2} 5-3x}\ &= \dfrac{\left(\displaystyle\lim_{x \to -2} x\right)\left(\displaystyle\lim_{x \to -2} x\right)\left(\displaystyle\lim_{x \to -2} x\right) + 2\left(\displaystyle\lim_{x \to -2} x\right)\left(\displaystyle\lim_{x \to -2} x\right) - \displaystyle\lim_{x \to -2} 1}{\displaystyle\lim_{x \to -2} 5 - 3\displaystyle\lim_{x \to -2} x}\ &= \dfrac{(-2)(-2)(-2) + 2(-2)(-2) - 1}{5 - 3(-2)}\ &= \ans{-\dfrac{1}{11}} \end{aligned}

Notice in both examples that the final line before the answer looks just like it would if we simply evaluated the original function at the point where we're taking the limit.

If f(x)f(x) is a polynomial or rational function and cc is in the domain of ff, then limxcf(x)=f(c)\displaystyle\lim_{x \to c} f(x) = f(c).

This actually isn't the full story; this doesn't just apply to polynomials and rational functions, but rather to all continuous functions. We just haven't defined continuity yet, and in fact, we'll use limits to do so, so it would be a bit circular to state that here. Just know that when we encounter continuity a bit later, its definition will be basically that it follows this pattern.

The bottom line, though, is simply this: if you can evaluate the function at cc, and the function is well-behaved, that's the same as the value of the limit.

Evaluate limx15x43x2+8x6x+1\displaystyle\lim_{x \to 1} \dfrac{5x^4-3x^2+8x-6}{x+1}.

Solution

Since this is a rational function, let's try evaluating it at x=1x=1; if that works, we'll have our answer.

limx15x43x2+8x6x+1=5(1)43(1)2+8(1)6(1)+1=42=2\begin{aligned} \lim_{x \to 1} \dfrac{5x^4-3x^2+8x-6}{x+1} &= \dfrac{5(1)^4 - 3(1)^2 + 8(1) - 6}{(1) + 1}\ &= \dfrac{4}{2}\ &= \ans{2} \end{aligned}

As it turns out, this also applies to one-sided limits, which get interesting when we look at piecewise-defined functions. The key there is to think about which definition applies on each side of the point at which we're looking for the limit.

One-Sided Limits

Find the one-sided limits at x=1x=1 for the following function: f(x)={2x+4 if x1x21 if x>1f(x) = \left{\begin{array}{rl} -2x+4 & \textrm{ if } x \leq 1\ x^2-1 & \textrm{ if } x > 1 \end{array}\right.

Solution

For the left-sided limit, the first definition applies, so as far as this limit knows, we should just plug in x=1x=1 to 2x+4-2x+4. Notice that both of these definitions are polynomials, so nothing strange is happening.

limx1f(x)=2(1)+4=2\lim_{x \to 1^-} f(x) = -2(1)+4 = \ans{2}

Similarly, for the right-sided limit, we can just plug x=1x=1 into x21x^2-1: limx1+f(x)=121=0\lim_{x \to 1^+} f(x) = 1^2-1 = \ans{0}

Because these two limits don't agree, by the way, the two-sided limit does not exist: limx1f(x) DNE\lim_{x \to 1} f(x) \textrm{ DNE}

  1. Find the one-sided limits at x=1x=1 for the following function: f(x)={x+1 if x = 1π if x=1f(x) = \left{\begin{array}{rl} x+1 & \textrm{ if } x\ \cancel{=}\ 1\ \pi & \textrm{ if } x = 1 \end{array}\right.

  2. limx1f(x)=1+1=2\lim_{x \to 1^-} f(x) = 1 + 1 = \ans{2} limx1+f(x)=1+1=2\lim_{x \to 1^+} f(x) = 1 + 1 = \ans{2}

Evaluating Limits Algebraically

What if plugging in the limit point doesn't work? For instance, consider the following limit: limx2x26x+8x24\lim_{x \to 2} \dfrac{x^2-6x+8}{x^2-4}

Since x=2x=2 is not in the domain of this function, the rule we used for the last few examples doesn't apply. In this case, though, we notice that we can simplify the function by factoring and canceling.

x26x+8x24=(x4)(x2)(x+2)(x2)=(x4)(x2)(x+2)(x2)=x4x+2\begin{aligned} \dfrac{x^2-6x+8}{x^2-4} &= \dfrac{(x-4)(x-2)}{(x+2)(x-2)}\ &= \dfrac{(x-4){\color{red}\cancel{(x-2)}}}{(x+2){\color{red}\cancel{(x-2)}}}\ &= \dfrac{x-4}{x+2} \end{aligned}

Is that really right, though?

Is it true that if f(x)=x26x+8x24f(x) = \dfrac{x^2-6x+8}{x^2-4} we can just write f(x)=x4x+2?f(x) = \dfrac{x-4}{x+2}?

It's almost correct, but there's a small caveat. When we write down a function, we generally assume that the domain is all the real numbers that can be evaluated. So in the first case, we'd notice that x=2x=2 and x=2x=-2 are both invalid, so the domain doesn't contain either point. In the second case, it only appears that x=2x=-2 is not in the domain. So these functions are not exactly equal, because their domains aren't equal. In fact, at every point other than x=2x=2, they are equal, but one is implicitly defined there and the other isn't.

The good news

Happily, this doesn't pose a problem when we're looking at limits. Since the limit doesn't see what happens exactly at x=2x=2 anyway, we can use the simplified version to evaluate the limit. In essence, when we simplify the function by canceling, we're filling in a hole in the graph.

The punchline

It may seem that we're spending a lot of space on a simple issue, but this is important because most of the limits we'll do in the future will involve some algebraic simplification, so it's important to understand why that works.

If we try to evaluate a limit by plugging in the point in question, and the function returns 00\dfrac{0}{0} that means there's something that can be cancelled from the top and bottom, and the simplified form will be something we can evaluate: the limits will be the same, so by evaluating the simpler version, we get the answer to the more complicated one we wanted.

Evaluate the following limit. limx2x26x+8x24\lim_{x \to 2} \dfrac{x^2-6x+8}{x^2-4}

Solution

limx2x26x+8x24=limx2(x4)(x2)(x+2)(x2)=limx2(x4)(x2)(x+2)(x2)=limx2x4x+2=242+2=12\begin{aligned} \lim_{x \to 2} \dfrac{x^2-6x+8}{x^2-4} &= \lim_{x \to 2} \dfrac{(x-4)(x-2)}{(x+2)(x-2)}\ &= \lim_{x \to 2} \dfrac{(x-4){\color{red}\cancel{(x-2)}}}{(x+2){\color{red}\cancel{(x-2)}}}\ &= \lim_{x \to 2} \dfrac{x-4}{x+2}\ &= \dfrac{2-4}{2+2}\ &= \ans{-\dfrac{1}{2}} \end{aligned}

Evaluate the following limit: limh0(3+h)29h\lim_{h \to 0} \dfrac{(3+h)^2-9}{h}

Solution

Notice that we're facing the same problem here as last time: if we try to evaluate the limit by plugging in h=0h=0, we get 0/00/0. This tells us that there's something to cancel, but we have to first expand the quadratic on top before we can factor and cancel: limh0(3+h)29h=limh09+6h+h29h=limh06h+h2h=limh0h(6+h)h=limh0h(6+h)h=limh06+h=6+0=6\begin{aligned} \lim_{h \to 0} \dfrac{(3+h)^2-9}{h} &= \lim_{h \to 0} \dfrac{9+6h+h^2-9}{h}\ &= \lim_{h \to 0} \dfrac{6h+h^2}{h}\ &= \lim_{h \to 0} \dfrac{h(6+h)}{h}\ &= \lim_{h \to 0} \dfrac{{\color{red}\cancel{h}}(6+h)}{{\color{red}\cancel{h}}}\ &= \lim_{h \to 0} 6+h\ &= 6 + 0 = \ans{6} \end{aligned}

Evaluate the following limit: limx2x2\lim_{x \to 2} \sqrt{x-2}

Solution

Think about evaluating this limit by plugging in values just larger and just smaller than 22. For values on the right side, this is no problem; the function approaches 00. But for the ones on the left, the function doesn't return anything, because that would require taking the square root of a negative number.

Since those values don't belong to the domain, we can only do the right-sided limit and not the left-sided limit, so the two-sided limit does not exist: limx2x2 DNE\ans{\lim_{x \to 2} \sqrt{x-2} \textrm{ DNE}}

  1. limx22x2+1x2+6x4\displaystyle\lim_{x \to 2} \dfrac{2x^2+1}{x^2+6x-4}

  2. 34\dfrac{3}{4}

  3. limx2x2+x6x2\displaystyle\lim_{x \to 2} \dfrac{x^2+x-6}{x-2}

  4. 55

  5. limx4x24xx23x4\displaystyle\lim_{x \to 4} \dfrac{x^2-4x}{x^2-3x-4}

  6. 45\dfrac{4}{5}

  7. limx1x31x21\displaystyle\lim_{x \to 1} \dfrac{x^3-1}{x^2-1}

  8. 32\dfrac{3}{2}

  9. limh0(4+h)216h\displaystyle\lim_{h \to 0} \dfrac{(4+h)^2-16}{h}

  10. 88